ECTHR_COMMITTEE 8445/20 vom 26. März 2026 , AFFAIRE KUZNETSOV ET PANOV c. RUSSIE - Ecthr Committee (2026)
Violation de l'article 2 - Droit à la vie (Article 2-1 - Enquête effective) (Volet procédural); Violation: 2;2-1